A Kind of Lidar Application Grid Based on eScience’s View - Deng Guang; Liu Qingwang; Li Zengyuan; Zhang Xu; Huang Zhenchun (Institute of Advanced Engineering and Science, 2012)
eScience means sharing documents、information and knowledge in research team and makes convenience to cooperate working. Further more, eScience becomes a social research platform open to anyone who is interested in specifically subject and can easily participate in it. The goal of this paper is to put up a web based distributed forest lidar processing service for forest researchers. Through a dedicated web portal users can have easy and fast access to the different service regardless the place where they are physically located. The main forest stand average height extracting algorithm encapsulated to service is integrated in a grid based infrastructure by using SIGRE middleware and SIGApp middleware. The workflow of this experiment system and results are be set out and discussed. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1348